New species of Bulbophyllum (Orchidaceae) in the flora of Vietnam Ⅱ - Averyanov, Leonid V.; Nguyen, Khang Sinh; Truong, Ba Vuong; Nguyen, van Canh; Maisak, Tatiana V.; Thai, Tran Huy; Dat, Pham Thi Thanh; Tu, Bao Ngan (Phytotaxa, 2019)
Three species, Bulbophyllum layae, B. metallica and B. papilligerum (all from sect. Cirrhopetalum) are described as new for science. All of these novelties are local endemics of limestone areas of northern Vietnam. Additionally, three species, B. alcicorne (sect. Brachystachya), B. psittacoglossum and B. yunnanense (both from sect. Sestochilus) are recorded for the flora of Vietnam for the first time. These species have wide distribution in mainland Asia. Data on ecology, phenology, distribution, brief relevant taxonomic notes, as well as color photographs, analytical plates of the type and voucher specimens are provided for all reported taxa. Lectotypification is provided for B. yunnanense.